Gastrointestinal Bleeding in Patients with HeartWare Ventricular Assist Device: Does the Activation of the Lavare Cycle Make a Difference?. Issue 1 (January 2018) - Saeed, Diyar; Maxhera, Bujar; Sadat, Najla; Petrov, Georgi; Albert, Alexander; Lichtenberg, Artur
Abstract : We aimed to investigate the prevalence of gastrointestinal bleeding (GIB) events in patients supported with HeartWare ventricular assist device (VAD) and activated lavare cycle. Thirty-two GIB events were documented in 22 patients (21%) after median support duration of 22 days (IQR: 11–157 days). There were 13 patients with early episodes of GIB. Meanwhile, 17 GIB events were documented in 9 patients after a median support duration of 174 days (IQR 25–736 days) (late bleeders), accounting for 0.18 events per patient's years. The GIB events appear to be a frequent complication in patients with HeartWare VAD regardless of the lavare cycle.